Population Growth and Economic and Social Development : Addresses - Clausen, A. W. (World Bank, Washington, DC, 2017)
These two addresses to the National Leaders’ Seminar on Population and Development in Nairobi and to the International Population Conference in Mexico City in 1984 concern the urgent and important problem of fast population growth. Rapid population growth slows development, with the poor being the principal victims as hundreds of millions of people will have lower living standards. Reducing population growth raises difficult public policy questions in the areas of family and fertility. In the past ten years, many developing countries have shown that quick, effective measures can be taken to reduce fertility, particularly widespread education of women, and easier access to contraception.